2011
DOI: 10.1021/la200136t
|View full text |Cite
|
Sign up to set email alerts
|

Cell Adhesion on Nanotextured Slippery Superhydrophobic Substrates

Abstract: In this work, the response of Saos2 cells to polymeric surfaces with different roughness/density of nanometric dots produced by a tailored plasma-etching process has been studied. Topographical features have been evaluated by atomic force microscopy, while wetting behavior, in terms of water-surface adhesion energy, has been evaluated by measurements of drop sliding angle. Saos2 cytocompatibility has been investigated by scanning electron microscopy, fluorescent microscopy, and optical microscopy. The similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 27 publications
1
38
0
2
Order By: Relevance
“…static non-flow conditions) on superhydrophobic surfaces. Di Mundo et al have shown that SaOs2 cells are inhibited on nanotextured hydrophobic surfaces, while they seem to adhere on slippery superhydrophobic surfaces with larger nanofeatures [186]. Similarly Cha et al [187] have shown that stems cells adhere on lotus leave micro-nano textured polystyrene.…”
Section: Cells On Nanostructured Surfaces and Antifoulingmentioning
confidence: 97%
“…static non-flow conditions) on superhydrophobic surfaces. Di Mundo et al have shown that SaOs2 cells are inhibited on nanotextured hydrophobic surfaces, while they seem to adhere on slippery superhydrophobic surfaces with larger nanofeatures [186]. Similarly Cha et al [187] have shown that stems cells adhere on lotus leave micro-nano textured polystyrene.…”
Section: Cells On Nanostructured Surfaces and Antifoulingmentioning
confidence: 97%
“…Di Mundo et al [139] studied how an osteoblast cell line (Saos2) responded to different roughness and densities of nanometer-sized dots. A decrease in cell adhesion is observed with increased roughness level (decrease in nanodot size).…”
Section: Cellular Interactionsmentioning
confidence: 99%
“…For example, it affects wetting and optical properties of surfaces, [4,5] the adsorption of proteins on surfaces, [6,7] and the cell adhesion and growth. [8,9] The importance of roughness motivated several studies on plasma induced surface roughness of polymeric substrates; [10][11][12][13][14][15][16][17][18][19][20] the focus was on recipes eliminating or producing roughness and on the mechanisms of roughness creation and evolution.…”
Section: Introductionmentioning
confidence: 99%